Fruit tracking between sites and years by birds in Mediterranean wintering grounds (Ecography, 2008)
Knowledge of the ability of birds to track spatiotemporal variation in fruit distribution is essential for understanding plant-frugivore interactions. Arguably, although total fruit availability sets an upper limit to the number of birds that can exploit a habitat patch, not all species can equally distribute abundance according to variation in fruit resources. To explore this, we studied bird and fruit abundance in 1999–2005 in Mediterranean scrublands and woodlands of southern Spain. We analysed whether changes of fruit abundance in eight different sites during six winters could predict numerical changes of a set of frugivorous passerines of the area (blackcap Sylvia atricapilla, Sardinian warbler S. melanocephala, robin Erithacus rubecula, song thrush Turdus philomelos and blackbird T. merula). We also investigated if all frugivores together tracked fruits better than individual species, thereby supporting a shared use of resources. Results showed strong inter-specific differences. Only the most abundant species (blackcaps and robins) tracked the spatial patterning of food despite strong differences in the use of space (vagrant and territorial, respectively). This suggests plastic behaviour of territorial robins, with individuals changing from strictly territorial to wandering, a flexibility that would favour between-site numerical arrangements according to food resources. Annual changes in bird numbers were independent of the availability of fruits, except for blackcaps, an abundant vagrant bird that tracked inter-winter changes in fruit abundance. The abundance of blackcaps fitted the spatiotemporal patterning of fruit resources better than the whole guild of frugivorous birds, inconsistent with the idea that these species track together the changing availability of fruit resources.